Opa e fusão - Salgado, Domingos Homem de Sousa e Holstein (2015)
Control of a public company can be obtained through several ways, of which the tender offer and the merger are only two. We attempt to understand what are the risks involved in the appearance of a control position. Such underlying risks justify the rationality of the mandatory bid rule, as well as the consequences of said rule. Finally, we attempt to understand if the interests of the minority shareholders are duly defended in the case of control being acquired through merger, since that is the understanding of the legislator.